A Ricoeurian analysis of identity formation in Philippians narrative, testimony, contestation - Yip, Scott Ying Lam (London T&T Clark, 2023)
Scott Ying Lam Yip presents the first specialized narrative study devoted to the identity formation processes in Philippians, based on Paul Ricoeur's narrative theory. Yip demonstrates that the "Christian identity" of the Philippian community is shaped amidst competing narratives with divergent comprehensions, and suggests that it is within an intra-Jewish contestation of testimonies that Paul updates his understanding of God and contends with a group of Jewish Christian leaders regarding the meaning of his suffering. Yip argues that Paul faces a double contestation of narrative in which both the political authorities and a group of Jewish Christian leaders see his imprisonment as futile and unnecessary; alerting him to an emerging crisis in which the Philippian community's conviction in suffering with him has begun to decline. It is thus essential for Paul to synthesise and install a new paradigmatic story of Christ so that his suffering can be discerned as the defining mark of God's renewed manifestation in an era of Christ's eschatological Lordship. Yip explores the means by which Paul - in a contestation of authority for the re-appropriation of God's past work - contrasts the future-oriented temporality of his testimony with the past-oriented one of the Jewish Christian leaders. He concludes that Paul affirms the value of his present suffering in truthfulness and installs his testimony to be the exemplary story for the Philippian community
Abbreviations List of Figures Introduction Chapter 1. Critical Review of Narrative Analyses of Philippians Chapter 2. Brief Review of Introductory Issues Chapter 3. Contestation of Temporalities, Identities and Testimonies: Ricoeur's Narrative Theory Chapter 4. Nature And Background of the Problem--Double Contestation of Narratives (Phil. 1:3-2:4) Chapter 5. Contestation of the Manifestation of God--The Paradigmatic Story of Christ (Phil. 2:5-11, 3:17-21) Chapter 6. Contestation of Temporalities--The Exemplary Story of Paul (Phil. 3:1-21) Chapter 7. Voluntary Re-Telling of Paul's Testimony (Phil. 2:12-16a) Chapter 8. The Stages of the Philippian Community's Collective Identity-Formation Chapter 9. Conclusion Bibliography Index
Barrierefreier Inhalt: Compliant with Level AA of the Web Content Accessibility Guidelines. Content is displayed as HTML full text which can easily be resized or read with assistive technology, with mark-up that allows screen readers and keyboard-only users to navigate easily
Keywords: Bible. Philippians -- Commentaries; Biblical studies & exegesis